Conceptual Analysis of Food Safety Based on Ethical and Legal Perspectives in the Qur'an and Hadith - Kharis Nugroho; Zaduna Fiddarain; Muhammad Hilmie; Miftah Khilmi Hidayatulloh (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
This study explores the relevance of the halal and tayyib principles in the Qur'an and Hadith to modern food safety issues. A qualitative approach with a descriptive-analytical design was employed to analyze Qur'anic texts, Hadiths, and relevant secondary literature. Data were collected through document analysis and analyzed using deductive-inductive methods to identify the relationship between Islamic teachings and contemporary food safety practices. The findings reveal that the principles of halal and tayyib encompass legality, quality, cleanliness, and food safety dimensions. Verses such as Surah Al-Baqarah (2:172) and Surah Al-Maidah (5:88) emphasize the importance of consuming food that is halalan thayyiban. The Hadiths on cleanliness and covering food containers align with modern food safety practices, such as contamination prevention. Additionally, literature indicates that consumers associate the halal label with high-quality and safe food standards. This study concludes that Islamic principles like halalan thayyiban can serve as theoretical and practical guidelines to address current food safety challenges. The research contributes to Islamic knowledge by offering a framework to integrate religious values into modern food safety systems. The findings open opportunities for future research, including field studies, cross-cultural collaboration, and the application of technology in halal certification.